2020
DOI: 10.1186/s12889-020-08974-1
|View full text |Cite
|
Sign up to set email alerts
|

Personalising screening of sight-threatening diabetic retinopathy - qualitative evidence to inform effective implementation

Abstract: Background: Internationally, systematic screening for sight-threatening diabetic retinopathy (STDR) usually includes annual recall. Researchers and policy-makers support extending screening intervals, citing evidence from observational studies with low incidence rates. However, there is little research around the acceptability to people with diabetes (PWD) and health care professionals (HCP) about changing eye screening intervals. Methods: We conducted a qualitative study to explore issues surrounding acceptab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Our parallel social science study demonstrated the acceptability of variable-interval, risk-based screening to individuals with diabetes and health professionals, provided that additional monitoring and fail-safe mechanisms are included [37]. Further evaluation should include the effect of factors such as the unexplained heterogeneity among screening programmes in England in terms of grading outcomes and screening uptake.…”
Section: Discussionmentioning
confidence: 82%
“…Our parallel social science study demonstrated the acceptability of variable-interval, risk-based screening to individuals with diabetes and health professionals, provided that additional monitoring and fail-safe mechanisms are included [37]. Further evaluation should include the effect of factors such as the unexplained heterogeneity among screening programmes in England in terms of grading outcomes and screening uptake.…”
Section: Discussionmentioning
confidence: 82%
“…Patients’ understanding of the purposes of dental visiting and the links this has with dental visiting behaviors shows strong similarities with studies on preventive visiting in general medical care services. The concept of preventive visits as insurance, with the health care provider viewed as taking responsibility for maintaining health, has similarly been found in patients’ accounts of eye screening ( Byrne et al 2020 ). This may underlie in part patients’ preferences toward dental visits at standard, regular intervals compared with risk-based intervals ( Fee et al 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…This may underlie in part patients’ preferences toward dental visits at standard, regular intervals compared with risk-based intervals ( Fee et al 2020 ). The use of risk-based intervals between preventive visits rather than standardized intervals is contested by patients in various areas of preventive health care visits, due in part to worries about longer intervals not being sufficient for preventing disease, cynicism about cost-saving motives on the part of health care services rather than health promotion motives, and regular visits being seen as an important motivation for self-care maintenance ( He et al 2018 ; Byrne et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was applied to 179 patients with T1DM, but their results did not report the cohort by type of DM, so we do not know if they were as effective in the case of patients with T1DM as in the rest of the sample, which included a total of 4538 patients with DM. 17 , 22 …”
Section: Discussionmentioning
confidence: 99%